Gaya Komunikasi Analisa Widyaningrum dan Efeknya Terhadap Publik - Anita Reta Kusumawijayanti; Sunardi, Afifah Mei (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2022)
Communication is the main point to create harmony in social life. Every person has a uniqueness and distinctiveness that is manifested in their communication styles. In the digital era, youtube has become one of the supporting media so that the messages conveyed are more effective, especially to reach the community or the public. Analisa Widyaningrum is a psychologist as well as a public figure who has succeeded in utilizing YouTube's social media as a channel for his message. Analisa is also known as a trainer, educator as well as director & founder at Analisa Personality Development Center (APDC), which is a psychological service center that focuses on mental health and individual self- development. This research uses a qualitative approach. This study is expected to be able to examine how Analisa Widyaningrum when communicating through his YouTube Channel, namely Analisa Channel, as well as knowing the effect of the message conveyed for viewers of Channel Analisa. YouTube is the main source of this research with observation and various libraries. The research was concluded that Analisa Widyaningrum used two communication styles, the equalitarian style (two-way) and the structuring style. While the effects include cognitive effects, affective effects related to attitudes or feelings and conative effects related to actions.